Comparison of the Effectiveness of Self-Esteem Training and Self-Control Skills Training on Academic Emotions and Academic Buoyancy among Sixth-Grade Male Elementary School Students in Falavarjan - Esmaili souderjani, Iman; Ghazanfari, Ahmad; Sharifi , Tayebeh (KMAN Counseling & Psychology Nexus, 2026)
The present study aimed to compare the effectiveness of self-esteem training and self-control skills training on academic emotions and academic buoyancy among sixth-grade male elementary school students in Falavarjan. This study employed a quasi-experimental design with a pretest–posttest structure, including a control group and a two-month follow-up period. The statistical population consisted of all sixth-grade male elementary school students in Falavarjan during the 2024–2025 academic year, from which 90 students were purposively selected. Ultimately, 75 participants were randomly assigned to two experimental groups and one control group. The research instruments included the Academic Emotions Questionnaire (Pekrun, Goetz, Titz, & Perry, 2002) for the hope subscale, the Epistemic Curiosity Questionnaire (Litman et al., 2010) for the curiosity subscale, the Empathy and Sympathy Scale (Vossen et al., 2015) for the empathy subscale, and the Academic Buoyancy Questionnaire (Dehghanizadeh et al., 2014). The two experimental groups received self-esteem training and self-control skills training in 8 and 10 sessions of 90 minutes each, respectively. Data were analyzed using repeated measures analysis of variance and Bonferroni post hoc tests. The results indicated that both self-esteem training and self-control skills training had a significant effect on academic emotions and academic buoyancy (p < .001). The effects of both interventions were maintained at the two-month follow-up stage. Furthermore, self-esteem training demonstrated greater effectiveness than self-control skills training in improving academic emotions (p < .001). However, no significant difference was found between the effectiveness of self-esteem training and self-control skills training on academic buoyancy (p > .05). The findings suggest that self-esteem training should be prioritized over self-control skills training for enhancing academic emotions among sixth-grade male students. Additionally, both self-esteem training and self-control skills training can be effectively utilized to improve academic buoyancy.